Critical Role of Soil Moisture Memory in Predicting the 2012 Central United States Flash Drought - Liang, Miaoling; Yuan, Xing (Frontiers in Earth Science, 2021)
The unprecedented 2012 summer drought over central USA was characterized by rapid intensification and severe impact, and was known as a flash drought. Since then, flash drought has raised a wide concern, with considerable progresses on the definition, detection of anthropogenic footprints, and assessment of ecological impact. However, physical mechanisms related to the flash drought predictability remain unclear. Here we show that the severity of the 2012 flash drought will be heavily underestimated without realistic initial soil moisture condition. The global Weather Research and Forecasting model (GWRF) was employed during the summers of 1979-2012, driven by observed sea surface temperature but without lateral boundary controls, which is similar to two-tier global seasonal prediction. The 2012 USA drought pattern was roughly captured by the GWRF ensemble global simulations, although with obvious underestimation of the severity. To further diagnose the role of soil moisture memory, dry and wet simulations that decreases and increases initial soil moisture by 10% were conducted. While the dry case does not significantly differ from the control case, the wet case totally missed the drought over central and southern Great Plain by changing the anticyclonic circulation anomaly to a cyclonic anomaly, and simulating a northward anomaly of meridional wind that brought anomalous moisture from Gulf of Mexico and finally resulted in a failure to predict the drought. This study highlights the importance of soil moisture memory in predicting flash drought that often occurred without strong oceanic signal.